(untitled) (ACTA MEDICA PERUANA, 2024)
We investiga te the incidence and clinical symptoms orthe Dengue epidemy ocurred between March and September 1990, we made the present study at the Medical Department of the Tarapoto Hospital Support, in 136 hospitalized patients. In our study 63.23% were women. The average age was 33.54 ± 12.36 years old, being more frecuent between 20 and 29 years old (38.96 % ). 76.47 % were hospitalized in May and J une. 81.63 % carne from the San Martin city. The most frequent ocupation was housekeeping (32.29%) and employees (28.67% ). The average time of disease was 4.77 ± 2.85 days. The clinical was fever (100%), musculoskeletal pain (77.94%), nausea and vomiting (69.12%), severe headache (61.91 % ), asthenia (41.16% ), pathologic bleeding (33.82 % ) and anorexia (21.32 % ). The patients were hospitalized with initial dlagnostic of virosis (35.29.29% ), dengue (28.69%), rever syndrome (10.29%) and acute gastroenterocolitis ( 4.41 % ). The patients received ru-stanalgesics -antipiretics (72.05 % ),antiemetics (55.88 % ), endovenous fluids (35.29 % ) and antiacids (33.82 % ). The symptomatic period was 4.03 ± 2.45 days.